Integrodifferential evolution systems with nonlocal initial conditions - KOUMLA, Sylvain; PRECUP, Radu (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The paper deals with systems of abstract integrodifferential equations subject to general nonlocal initial conditions. In order to allow the nonlinear terms of the equations to behave independently as much as possible, we use a vector approach based on matrices, vector-valued norms and a vector version of Krasnoselskii’s fixed point theorem for a sum of two operators. The assumptions take into account the support of the nonlocal initial conditions and the hybrid character of the system. Two examples are given to illustrate the theory. Mathematics Subject Classification (2010): 34K30, 35K90, 47J35.